2012
DOI: 10.1016/j.yexcr.2012.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The role of cell–extracellular matrix interactions in glomerular injury

Abstract: Glomerulosclerosis is characterized by excessive deposition of extracellular matrix within the glomeruli of the kidney, glomerular cell death, and subsequent loss of functional glomeruli. While in physiological situations the levels of extracellular matrix components are kept constant by a tight balance between formation and degradation, in the case of injury that results in fibrosis there is increased matrix deposition relative to its breakdown. Multiple factors control matrix synthesis and degradation, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Deposition of collagen and fibronectin in tissues takes place in inflammatory bowel disease, asthma, scleroderma, lupus nephritis, and glomerulonephritis (11)(12)(13)(14). Significant increases in HA and proteoglycans have been observed in rheumatoid arthritis, inflammatory bowel disease, chronic inflammatory vascular disease, lupus nephritis, Graves ophtalmopathy, and type 1 diabetes (15)(16)(17)(18)(19)(20).…”
Section: Ecm In Inflammationmentioning
confidence: 99%
“…Deposition of collagen and fibronectin in tissues takes place in inflammatory bowel disease, asthma, scleroderma, lupus nephritis, and glomerulonephritis (11)(12)(13)(14). Significant increases in HA and proteoglycans have been observed in rheumatoid arthritis, inflammatory bowel disease, chronic inflammatory vascular disease, lupus nephritis, Graves ophtalmopathy, and type 1 diabetes (15)(16)(17)(18)(19)(20).…”
Section: Ecm In Inflammationmentioning
confidence: 99%
“…The intracellular region of α6β4 consists in the short tail of α6 and the large β4 cytodomain, which is responsible for the interactions with plectin and collagen XVII in keratinocytes. The ligands of α6 integrin include CD151, collagen XVII and laminin 332. α6β4 not only performs a major adhesive function in cells but also promotes polarization, a final event in epithelial cell differentiation (Borza and Pozzi 2012).…”
Section: Junctional Eb With Pyloric Atresiamentioning
confidence: 99%
“…No human diseases are directly attributed to mutations in these integrins; however, a large body of evidence suggests that their expression is altered in the course of human kidney disease and that they modulate renal fibrosis in rodents. 20 The first evidence that collagen-binding receptors regulate renal fibrosis comes from studies demonstrating that antiintegrin a1 antibodies reduce scarring in rat models of glomerular injury by inhibiting leukocyte function and the immune response. 21 It was subsequently shown that integrin a1-null mice have decreased glomerular fibrosis in a mouse model of Alport syndrome.…”
Section: The Collagen Receptorsmentioning
confidence: 99%